Short-offset grounded-wire TEM method for efficient detection of mined-out areas in vegetation-covered mountainous coalfields. Issue 4 (1st December 2017) - Zhou, Nannan; Xue, Guoqiang; Hou, Dongyang; Li, Hai; Chen, Weiying
Abstract : The in-loop transient electromagnetic (TEM) method has been widely used for reliable investigation of mined-out areas of the subsurface. However, the method has limited applications in mountainous coalfields that are often covered with tall vegetation: first, it requires extra work to clear the surface and set up the TEM equipment; more importantly, dense vegetation restricts the required layout of a standard rectangular loop, and such geometry irregularity can decrease the detection accuracy. This study proposes using short-offset grounded-wire TEM (SOTEM) for enhanced detection of the mined-out areas in vegetation-covered mountainous fields. The distance between the SOTEM source and receivers is flexible and thereby the receiving location can be freely adjusted according to the environmental conditions of the surveying area, without reducing the detection resolution. Properties of the proposed SOTEM method are well tested before real applications, and our test indicates that SOTEM has an axis-symmetric field distribution, higher sensitivity to anomaly, and larger detection depth, compared to the conventional large-loop TEM method. Application to one coalfield in Changzhi (Shanxi Province, China) demonstrates the added value of implementing SOTEM for detecting the mined-out areas in this field and the results are well verified by the drilling result. Abstract : The objective of this study was to overcome the limitations in using the loop-source TEM method and realise the efficient detection of mined-out areas using the short-offset grounded-wire TEM (SOTEM) method in vegetation-covered mountainous coalfields. The feasibility of SOTEM is verified by the drilling result in the field test.